2016
DOI: 10.2196/jmir.6484
|View full text |Cite
|
Sign up to set email alerts
|

A Diabetes Self-Management Program: 12-Month Outcome Sustainability From a Nonreinforced Pragmatic Trial

Abstract: BackgroundDiabetes self-management education has been shown to be effective in controlled trials. The 6-week Better Choices, Better Health-Diabetes (BCBH-D) self-management program was also associated with an improvement in health outcomes in a 6-month translation study.ObjectiveThe objective of this study was to determine whether a national translation of the BCBH-D self-management program, offered both Web-based and face-to-face, was associated with improvements in health outcomes (including HbA1c) and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(103 citation statements)
references
References 13 publications
1
101
0
1
Order By: Relevance
“…Evidence-based communication strategies such as collaborative goal setting, action planning, motivational interviewing, shared decision making, cognitive behavioral therapy, problem solving, selfefficacy enhancement, teach-back, and relapse-prevention strategies are also effective (120,(136)(137)(138)(139). It is crucial to develop action-oriented behavior change goals and objectives (130,140). Creative, person-centered, experience-based delivery methods beyond the mere acquisition of knowledge are effective for supporting informed decision making and meaningful behavior change and addressing psychosocial concerns (122,141).…”
Section: Standard 7 Individualizationmentioning
confidence: 99%
“…Evidence-based communication strategies such as collaborative goal setting, action planning, motivational interviewing, shared decision making, cognitive behavioral therapy, problem solving, selfefficacy enhancement, teach-back, and relapse-prevention strategies are also effective (120,(136)(137)(138)(139). It is crucial to develop action-oriented behavior change goals and objectives (130,140). Creative, person-centered, experience-based delivery methods beyond the mere acquisition of knowledge are effective for supporting informed decision making and meaningful behavior change and addressing psychosocial concerns (122,141).…”
Section: Standard 7 Individualizationmentioning
confidence: 99%
“…While there is potential for some biases between the full Lorig, et al, (2016) study sample and the claims sample based on sex, age, and format of treatment, on the whole, the claims identified cohort represents the original study population. [16] Impact of Diabetes Self-Management on Healthcare Costs 8 Baseline demographics and healthcare utilization data for post-match patients are presented in …”
Section: Identification Of Clinical Study Patients In Healthcare Claimentioning
confidence: 99%
“…Two related studies evaluating the small group and internet based BCBH-D program, led by a consortium of the Stanford Patient Education Research Center, National Council on Aging (NCOA), and Anthem Health Plans reported modest benefits among the program participants based on 6 and 12-month follow-up periods. [15,16] The 6-month follow-up study reported statistically significant improvements in 13 of 14 outcome measures, including HbA1c and health behaviors (e.g. communication with physicians, stretching/strengthening exercise, medication adherence, frequency of eye, foot, cholesterol and kidney exams).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations